CX3CR1 is a gatekeeper for intestinal barrier integrity in mice: Limiting steatohepatitis by maintaining intestinal homeostasis. Issue 5 (2nd September 2015) - Schneider, Kai Markus; Bieghs, Veerle; Heymann, Felix; Hu, Wei; Dreymueller, Daniela; Liao, Lijun; Frissen, Mick; Ludwig, Andreas; Gassler, Nikolaus; Pabst, Oliver; Latz, Eicke; Sellge, Gernot; et al.
<x xml:space="preserve">Abstract</x> Nonalcoholic fatty liver disease is seen as the hepatic manifestation of the metabolic syndrome and represents the most common liver disease in Western societies. The G protein–coupled chemokine receptor CX3CR1 plays a central role in several metabolic syndrome–related disease manifestations and is involved in maintaining intestinal homeostasis. Because diet‐induced intestinal dysbiosis is a driver for nonalcoholic fatty liver disease, we hypothesized that CX3CR1 may influence the development of steatohepatitis. In two independent models of diet‐induced steatohepatitis (high‐fat diet and methionine/choline‐deficient diet), CX3CR1 protected mice from excessive hepatic steatosis and inflammation, as well as systemic glucose intolerance. Lack of Cx3cr1 expression was associated with significantly altered intestinal microbiota composition, which was linked to an impaired intestinal barrier. Concomitantly, endotoxin levels in portal serum and inflammatory macrophages in liver were increased in Cx3cr1–/– mice, indicating an increased inflammatory response. Depletion of intestinal microbiota by administration of broad‐spectrum antibiotics suppressed the number of infiltrating macrophages and promoted macrophage polarization in liver. Consequently, antibiotic‐treated mice demonstrated a marked improvement of steatohepatitis. Conclusion: Microbiota‐mediated activation of the innate immune responses through CX3CR1 is crucial for controlling steatohepatitis progression, which recognizes CX3CR1 as an essential gatekeeper in this scenario. (Hepatology 2015;62:1405–1416)